Pressure-Induced Formation of Quaternary Compound and In−N Distribution in InGaAsN Zincblende from Ab Initio Calculation - Prayoonsak Pluengphon (2019)
© 2019 The Authors. Published by Wiley-VCH Verlag GmbH & Co. KGaA. We present the effects of In−N distribution and high pressure on the zincblende phase (0–5 GPa) of In x Ga 1−x As 0.963 N 0.037 (x=0.074, 0.111 and 0.148). Structural, electronic, and optical properties are analyzed, and it is found that non-isotropic distribution of In−N (type C) possesses the minimum free energy for the InGaAsN conventional cell system. An increasing indium content reduces the formation enthalpy of InGaAsN. The formation enthalpy, conduction band minimum, strength of covalent bonds, and electron density differences in free space of InGaAsN are decreased under high-pressure conditions. The dielectric performance and static permittivity of InGaAsN are lower than that of GaAs, for which the dielectric performance transforms to conductor performance at high frequency. The optimum photoabsorption coefficient is found at the composition of In 0.111 Ga 0.889 As 0.963 N 0.037 (3In−N), which very well relates to the literature.